Effects of Age, Housing Environment, and Strain on Physical Egg Quality Parameters of Laying Hens - B Tainika; A Şekeroğlu; A Akyol; YE Şentürk; SH Abaci; M Duman (Brazilian Journal of Poultry Science)
ABSTRACT This study examined the effects of age, housing environment, and strain (Lohmann Sandy (LS) and Lohmann LSL Classic (LW)) on egg quality traits. Deep litter (DL), free access to outdoor Mentha piperita (MP), Petroselinum crispum (PC), and Medicago sativa (MS) vegetated environments were examined. A total of 260 four-week-old birds were randomly distributed to DL and outdoor plant-associated groups, with four and three replicates, respectively, and 10 birds per replicate. Eggs were analyzed between 26 and 52 weeks of hen age, every 4 weeks. Overall, all egg quality parameters significantly differed as hen age increased (p<0.01). The housing environment significantly influenced egg weight, shell-breaking strength, shell thickness, egg surface area, and yolk color score. Eggs obtained from DL hens were heavier and had a higher egg surface area than those from MS, PC, and MP hens (p<0.01; p<0.05). However, eggs laid by MS, PC, and MP hens had higher shell-breaking strength and thickness (p<0.01; p<0.05). DL hens had a greater ratio of eggs with meat-blood inclusions in the yolk compared to MS, PC, and MP hens (p<0.05). Shape index, albumen height, albumen index, Haugh unit, and yolk index were similar among housing environments (p>0.05). Strain significantly affected shape index, shell thickness, albumen height, albumen index, Haugh unit, albumen pH, yolk index, and yolk color score. LS eggs had higher shape index, shell thickness, yolk index, and yolk color score (p<0.01; p<0.05). However, LW eggs had greater albumen height, albumen index, Haugh unit, and albumen pH (p<0.01; p<0.05). LW strain had a lower ratio of eggs with meat-blood inclusions compared to LS (p<0.01). Shell-breaking strength and egg surface area did not differ between hen strains (p>0.05). This study showed that allowing hens access to MS, PC, or MP plant species improved shell quality traits. Moreover, it appears that there is a greater genetic variability in albumen and yolk quality traits.